Paricalcitol Inhibits Wnt/β-Catenin Signaling Pathway and Ameliorates Dermal Fibrosis in Bleomycin Induced Scleroderma Model - Nevzat GÖZEL,; Fikret DURAN,; Ahmet YILDIRIM,; Servet YOLBAŞ,; Ebru ÖNALAN,; İbrahim Hanifi ÖZERCAN,; Süleyman Serdar KOCA, (Archives of Rheumatology, 2018)
Objectives: This study aims to determine the prophylactic and therapeutic efficacy of inhibition of Wnt/β-catenin signaling pathway with paricalcitol in an experimental scleroderma model created with bleomycin (BLM). Materials and methods: Sixty female BALB/c mice (8-week old and weighing 25 g to 30 g) were divided into six groups as prophylactic-early [group 1 (control I)], sham I (group 2), paricalcitol I (group 3), therapeutic-late [group 4 (control II)], sham II (group 5), and paricalcitol II (group 6) groups. Subcutaneous BLM (100 μg/day) injections were used to induce dermal fibrosis and paricalcitol (0.3 μg/kg/day) was applied subcutaneously to BLM-injected mice during the first three weeks for preventive interventions and in the second three weeks for therapeutic interventions. Tissue samples were harvested for subsequent pathological and real-time polymerase chain reaction analysis. Tissue transforming growth factor-beta 1, axin-1, and Wnt-2 messenger ribonucleic acid expressions were determined by real-time polymerase chain reaction. Results: Repeated BLM applications increased the dermal inflammatory cell infiltration and dermal thickness, and led to dermal fibrosis, in both early and late stages. Similarly, transforming growth factor-beta 1, axin-1, and Wnt-2 expressions were significantly increased in the sham groups compared to the own control group (p<0.05 for all). Contrarily, prophylactic and therapeutic paricalcitol applications decreased the transforming growth factor-beta 1, axin-1, and Wnt-2 messenger ribonucleic acid expressions compared to the own sham group (p<0.05 for all). In addition, the regressions in dermal necro-inflammation and dermal fibrosis on pathological views were also observed in the paricalcitol applied groups. Conclusion: In this model, increased axin-1 and Wnt-2 messenger ribonucleic acid expressions suggest that Wnt/β-catenin pathway is active in dermal fibrosis.